Sports behaviour and adherence to sports and exercise recommendations in patients with myocarditis - Matthias Wilhelm; Christoph Gräni; Catherine Gebhard; Jonathan Schütze; Benedikt Bernhard; Noah Greisser; Philippe Joss; Sarah Manser; Anselm W Stark; Isaac Shiri; Maryam Pavlicek (BMJ Open Sport & Exercise Medicine)
Aim In the clinical setting of acute myocarditis, existing guidelines recommend refraining from moderate-intensity to high-intensity sports for 3–6 months, yet the extent to which these recommendations are implemented by clinicians and followed by patients remains unclear.Methods From January 2020 to December 2023, consecutive patients with myocarditis according to European Society of Cardiology criteria were prospectively enrolled. Myocarditis was categorised into acute, subacute and non-acute myocarditis. Patients completed a sports questionnaire and sports behaviour was categorised into no sports (NSP), recreational (REC) or competitive sports (COMP).Results A total of 165 patients with myocarditis (mean age 50±17 years, 35% women) completed the questionnaire. Overall 73 (44%) patients received sports counselling. A total of 44 (72%) patients engaged in sports (REC+COMP) with acute or subacute myocarditis, received sports counselling with 38 (87%) adhering. Overall COMP patients (all male) received more counselling (11/11; 100%) compared with REC (53/105; 50%) and NSP (9/49; 18%). Of 39 women in the REC group, 14 (36%) received recommendations, whereas of 66 men 39 (59%) received recommendations (p<0.001). Of all patients engaged in sports, 55% received recommendations. Self-reported adherence to recommendations was significantly lower in COMP (73%) compared with REC (92%, p<0.001).Conclusion Although only half of the myocarditis patients received counselling regarding sports activity, adherence to these recommendations was generally high but varied by activity level. Women received fewer recommendations overall compared with men. While competitive athletes were counselled more frequently than recreational athletes, they were less likely to adhere to the recommendations.